2017
DOI: 10.1002/wrna.1449
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease Regnase‐1/Monocyte chemotactic protein‐1‐induced protein‐1 (MCPIP1) in controlling immune responses and beyond

Abstract: The activation of inflammatory cells is controlled at transcriptional and posttranscriptional levels. Posttranscriptional regulation modifies mRNA stability and translation, allowing for elaborate control of proteins required for inflammation, such as proinflammatory cytokines, prostaglandin synthases, cell surface co-stimulatory molecules, and even transcriptional modifiers. Such regulation is important for coordinating the initiation and resolution of inflammation, and is mediated by a set of RNA-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 109 publications
0
34
0
Order By: Relevance
“…mRNAs harboring a CDE are selectively recognized and rapidly degraded by the ring finger-and CCCH-type domain-containing protein known as roquin (Leppek et al 2013). Recent studies revealed that 3 ′ UTR CDEs are also recognized by the zinc finger CCCH-type containing 12a protein known as regnase 1 (also known as ZC3H12A, and originally identified as monocyte chemotactic protein-induced protein 1; Mino et al 2015;Takeuchi 2018). Regnase 1 contains a PilT amino-terminal (PIN)-like RNase domain (also called a NYN domain) that manifests endoribonuclease activity (Matsushita et al 2009).…”
Section: Regnase 1-mediated Mrna Decay (Rmd)mentioning
confidence: 99%
“…mRNAs harboring a CDE are selectively recognized and rapidly degraded by the ring finger-and CCCH-type domain-containing protein known as roquin (Leppek et al 2013). Recent studies revealed that 3 ′ UTR CDEs are also recognized by the zinc finger CCCH-type containing 12a protein known as regnase 1 (also known as ZC3H12A, and originally identified as monocyte chemotactic protein-induced protein 1; Mino et al 2015;Takeuchi 2018). Regnase 1 contains a PilT amino-terminal (PIN)-like RNase domain (also called a NYN domain) that manifests endoribonuclease activity (Matsushita et al 2009).…”
Section: Regnase 1-mediated Mrna Decay (Rmd)mentioning
confidence: 99%
“…In a similar fashion, a set of immune‐related RBPs harbor CCCH‐type zinc finger domains . Key examples of such RBPs include members of the ZFP36 family, Roquin‐1,2 and Regnase family (ZC3H12A‐D, MCPIP1‐4 or Regnase‐1‐4) …”
Section: Inflammation‐related Mrnas Are Regulated By a Set Of Rna Binmentioning
confidence: 99%
“…14 Key examples of such RBPs include members of the ZFP36 family, 15 Roquin-1,2 16 and Regnase family (ZC3H12A-D, MCPIP1-4 or Regnase-1-4). 17 TTP recognises AREs in the 3 0 UTR of target mRNAs via its two zinc finger domains and destabilises them by recruiting the carbon catabolite repression 4negative on TATA-less (CCR4-NOT) deadenylation complex via an evolutionarily conserved C-terminal motif. 18 TTP deficiency in mice leads to autoimmune symptoms, with cachexia and arthritis resulting from excess TNF production.…”
Section: Cis-elements In the 3 0 Utr Of Inflammatory Mrnasmentioning
confidence: 99%
“…This process, initiated by endoribonucleases including Regnase-1, generates bare 5 0 and 3 0 ends, which are targeted by the above-mentioned exonucleolytic enzymes. [33]. In addition, other RBPs which lack this domain have also shown to be involved in the regulation of immune reactions.…”
Section: Rna Binding Proteins Regulate the Pathology Of Autoimmune DImentioning
confidence: 99%